Effectiveness of wound healing using the novel collagen dermal substitute INSUREGRAF®. Issue 64 (23rd June 2016) - Yoon, Hyeon; Yang, Hyeong Tae; Yim, Haejun; Kym, Dohern; Hur, Jun; Yang, Eunkyung; Jung, Samhyun; Yang, Sunghee; Kim, Geunhyung; Kim, June-Bum; Chun, Wook; Cho, Yong Suk
Abstract : The pore structure of INSUREGRAF® built up from parallel collagen layers connected by single fivers and sizes are very uniform. Therefore, this is more suitable with respect to cell penetration, distribution, and acceleration of skin regeneration. Abstract : Collagen sponges are often used as dermal substitutes in the treatment of burns, trauma, infections, and wounds. Dermal substitutes that can be applied in a one-stage operation are particularly important for dermal regeneration. Some protocols for the production of collagen sponges have been developed, but many issues remain, including low yield, contraction, and expense. In this study, the effectiveness of two skin substitutes was evaluated. Specifically, we compared two thin matrices, i.e., the newly developed INSUREGRAF® 1.2 mm and the widely used Matriderm® 1 mm Single Layer, with respect to their biochemical and mechanical properties, safety, and efficacy. We examined the rate of contractibility and biocompatibility using in vitro and in vivo models. The INSUREGRAF had an interconnected pore structure, which affects cell attachment and proper vascularization. Accordingly, this novel collagen sponge type has the potential to promote skin tissue regeneration and is especially suitable for full-thickness skin defects as a one-stage operation substitute.